Characteristics of gadolinium doped cerium at different calcination temperatures for intermediate temperature SOFC - Damisih,; Hapsari, Ade Utami; Agustanhakri,; Deni, Yelvia; Arjasa, Oka Pradipta; Anggaravidya, Mahendra; Raharjo, Jarot; Mahendra Rao Somalu, (Penerbit Universiti Kebangsaan Malaysia, 2020)
Gadolinium doped cerium (Ce0.9Gd0.1O1.95 or GDC10) was successfully synthesized using the solid-state method. Commercially available CeO2 and Gd2 O3 powders were used as starting materials. They were mixed in a ball mill where alumina balls were added as grinding medium with the ratio to powders as of 1:2. The obtained powders were dried and then calcined at temperatures of 600, 700 and 800 °C, respectively. The objective of this research was to investigate the effects of calcination temperature on the properties of GDC10. The powders were characterized using XRF, TGA, XRD, and PSA instruments. XRF analysis shows the presence of Ce, Gd and O elements in stoichiometric composition without any impurities. XRD analysis showed single phase structure of CeO2 where the crystallite size and lattice parameter increases and decreases, respectively, as the calcination temperature increases. The smallest particle size of 647.3 nm was obtained at the calcination temperature of 600 °C. The density of all GDC10 samples sintered at 1350 °C was found to be higher than 95%. In addition, the calcination temperature also influenced the ionic conductivity where the highest obtained value was 0.0153 S.cm-1 at 800 °C for the sample calcinaed at 600 °C. The results suggest that the calcination temperature affected the properties of GDC10 for solid oxide fuel cell application.